The Histopathological Examination of the Degeneration of Menisci in Osteoarthritic Knees Using an Adapted Bonar Score: Does Osteoarthritis Equally Influence the Lateral and Medial Menisci? - Maria Zabrzyńska; Maciej Gagat; Paulina Antosik; Łukasz Woźniak; Michał Kułakowski; Karol Elster; Jan Zabrzyński (Applied Sciences, 2024)
This study aimed to investigate the degeneration of the meniscal tissue in osteoarthritic knees and to adapt the Bonar score and its modifications to develop a microscopic examination. This study included consecutive patients who underwent total knee arthroplasty for symptomatic end-stage gonarthrosis. During the surgery, the menisci were completely dissected to preserve their original shapes. The samples were prepared using the hematoxylin and eosin (H&E) staining method and the Alcian blue protocol and were examined under light microscopy. The extent of histopathological changes was assessed based on the classical Bonar score assumptions. Additionally, in the second step of the examination, menisci remnants were evaluated using the modified Bonar score developed by Zabrzyński et al. The study involved 44 patients, from whom 83 samples of knee menisci were obtained. Histological examination of the meniscal specimens under a light microscope revealed tissue degeneration in all cases, in both the medial and lateral menisci. The mean classical Bonar score was 8.3571 and the mean modified Bonar score was 6.9398. There were no statistically significant differences in classical Bonar score assessment between medial and lateral menisci (p = 0.3014). There were no statistically significant differences in the modified-Bonar score assessment between medial and lateral menisci (p = 0.3620). We show that both menisci are implicated in the degenerative process, with high scores in the Bonar system, regardless of knee axial deformity. The Bonar score, along with its modifications, can be readily employed in the microscopic assessment of meniscus pathology.